2023
DOI: 10.3390/nano13172479
|View full text |Cite
|
Sign up to set email alerts
|

Human Dental Pulp Mesenchymal Stem Cell-Derived Soluble Factors Combined with a Nanostructured Scaffold Support the Generation of a Vascular Network In Vivo

Ludovica Barone,
Matteo Gallazzi,
Federica Rossi
et al.

Abstract: Among all strategies directed at developing new tools to support re-vascularization of damaged tissues, the use of pro-angiogenic soluble factors, derived from mesenchymal stem cells (MSCs), appears a promising approach for regenerative medicine. Here, we compared the feasibility of two devices, generated by coupling soluble factors of human dental pulp mesenchymal stem cells (DPSCs), with a nanostructured scaffold, to support angiogenesis once transplanted in mice. DPSCs were obtained from impacted wisdom too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Although human clinical studies on DPSC are still relatively few due to reasons such as incompletely confirmed safety and cost of treatment, animal experiments on DPSC have been relatively abundant, which amply demonstrates their promising application in tissue engineering. Barone et al implanted DPSC and cell scaffolds into nude mice and found that the experimental group obtained better in vivo vascular network generation ( Barone et al, 2023 ). Yamaguchi et al applied DPSC intravenously to treat mice in an ischemia-reperfusion myocardial injury model and found that apoptosis and inflammation in cardiomyocytes were significantly suppressed ( Yamaguchi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although human clinical studies on DPSC are still relatively few due to reasons such as incompletely confirmed safety and cost of treatment, animal experiments on DPSC have been relatively abundant, which amply demonstrates their promising application in tissue engineering. Barone et al implanted DPSC and cell scaffolds into nude mice and found that the experimental group obtained better in vivo vascular network generation ( Barone et al, 2023 ). Yamaguchi et al applied DPSC intravenously to treat mice in an ischemia-reperfusion myocardial injury model and found that apoptosis and inflammation in cardiomyocytes were significantly suppressed ( Yamaguchi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%